Gender (a)symmetries: success and barriers in professional discourses - da Silva, Carla Alexandra F. (2021)
Gender influences career choices and life opportunities, creating different social expectations. The same is true of visions of success, reinforcing social and professional asymmetries between women and men. To understand how conceptions of gender translate into perceptions of professional success, we conducted nine interviews, in Portugal, with residents and workers. The discourses extracted by thematic analysis were organized into three themes interconnected by the concept of gender asymmetries. We have concluded that discursive practices communicate inflexibility in gender constructions that penalize women's career development due to the overload of domestic responsibilities and the devaluation of femininity in professional paths.